#1**+5 **

x+1/x=25

Solve for x:

x+1/x = 25

Bring x+1/x together using the common denominator x:

(x^2+1)/x = 25

Multiply both sides by x:

x^2+1 = 25 x

Subtract 25 x from both sides:

x^2-25 x+1 = 0

Subtract 1 from both sides:

x^2-25 x = -1

Add 625/4 to both sides:

x^2-25 x+625/4 = 621/4

Write the left hand side as a square:

(x-25/2)^2 = 621/4

Take the square root of both sides:

x-25/2 = (3 sqrt(69))/2 or x-25/2 = -(3 sqrt(69))/2

Add 25/2 to both sides:

x = 25/2+(3 sqrt(69))/2 or x-25/2 = -(3 sqrt(69))/2

Add 25/2 to both sides:

**Answer: |x = 25/2+(3 sqrt(69))/2 or x = 25/2-(3 sqrt(69))/2**

x^2+1/x^2=?

Simplify the following:

x^2+1/x^2

Put each term in x^2+1/x^2 over the common denominator x^2: x^2+1/x^2 = x^4/x^2+1/x^2:

x^4/x^2+1/x^2

x^4/x^2+1/x^2 = (x^4+1)/x^2:

**Answer: |(x^4+1) / x^2**

Guest Feb 13, 2016

#1**+5 **

Best Answer

x+1/x=25

Solve for x:

x+1/x = 25

Bring x+1/x together using the common denominator x:

(x^2+1)/x = 25

Multiply both sides by x:

x^2+1 = 25 x

Subtract 25 x from both sides:

x^2-25 x+1 = 0

Subtract 1 from both sides:

x^2-25 x = -1

Add 625/4 to both sides:

x^2-25 x+625/4 = 621/4

Write the left hand side as a square:

(x-25/2)^2 = 621/4

Take the square root of both sides:

x-25/2 = (3 sqrt(69))/2 or x-25/2 = -(3 sqrt(69))/2

Add 25/2 to both sides:

x = 25/2+(3 sqrt(69))/2 or x-25/2 = -(3 sqrt(69))/2

Add 25/2 to both sides:

**Answer: |x = 25/2+(3 sqrt(69))/2 or x = 25/2-(3 sqrt(69))/2**

x^2+1/x^2=?

Simplify the following:

x^2+1/x^2

Put each term in x^2+1/x^2 over the common denominator x^2: x^2+1/x^2 = x^4/x^2+1/x^2:

x^4/x^2+1/x^2

x^4/x^2+1/x^2 = (x^4+1)/x^2:

**Answer: |(x^4+1) / x^2**

Guest Feb 13, 2016